Glosa do postanowienia SR dla Wrocławia Fabrycznej we Wrocławiu z 13.2.2023 r. WR.VI NS-REJ.KRS/000574/23/367. Wielość systemów teleinformatycznych w rozumieniu ustawy o KRS i brak interoperacyjności – negatywne skutki dla strony postępowania rejestrowego - Skrzywanek, Michał (Wydawnictwo C.H. Beck)
The subject of this article is to discuss the negative consequences experienced by parties involved in proceedings to amend entries in the National Court Register due to the lack of interoperability mandated by law regarding the existence of several ICT systems within the meaning of the National Court Register Act. These consequences – consisting of a refusal to amend the entry in the business register – are all the more unacceptable in a democratic state governed by the rule of law, as it is solely the citizen, the participant in the proceedings, who has been entirely burdened with the consequences of technical failures attributable to the Minister of Justice.
Keywords: interoperability; National Court Register; Court Registers Portal (PRS); National Court Register Act; application for amendment of entry in the business register; voluntary redemption of shares; limited liability company